Estágio Profissional: O aluno que se tornou Professor - Carlos Filipe Azevedo Moleiro (2020)
As part of the study plan for the 2nd year of the Master in Physical Education Teaching in Elementary and Secondary Education at the Faculty of Sports of the University of Porto, the Professional Internship allows to put into practice the knowledge and skills acquired during the initial formation in a real teaching context, where a daily confrontation with the constraints that the teaching profession entails exists. Likewise, it allows a progressive entry into the career, being guided by experienced professionals. This document, Internship Report, intends to manifest the evolutionary process of the trainee teacher, as he finds new responsibilities, problems, solutions and/or dilemmas, among others, portraying his personal experience throughout the school year. The construction of this document was structured in different chapters. It begins with an Introduction, which frames the document and informs about the proposed objectives. Then comes the Biographical Framework, it shows a more personal side, allowing a reflection on the past and the influence on the objectives proposed today, on what were the career choices and expectations for the same. The third point encompasses the Institutional Framework, which shows the context in which the Professional Internship was carried out and how its characteristics shaped what I was as a teacher. After the framing, arises the Organization and Management of Teaching and Learning, an area in which the great pedagogical processes are carried out, and Participation in School and Relationship with the Community, which refers to the influence of this participation in the global development of the profile the trainee teacher. Finally, Conclusions and Future Perspectives close the document, presenting ambitions and making a balance through the lessons learned from the internship year. The realization of this stage is the culmination of yet another objective, which has allowed me a striking evolution in what I will be, not only as a teacher, but in all parameters of my life.